Strengthening Critical Thinking Skills of Prospective Teacher Students through Inquiry Learning in Science Learning: An Explanatory Mixed Methods Study - Aisyah Ali; Singgih Bektiarso; Auldry Fransje Walukow; Erlia Narulita; Akhmad Kadir (Postgraduate, University of Mataram, 2025)
This study aims to explore the effectiveness of Inquiry-Based Learning (IBL) integrated with the local culture of Hem Re Yegokhe in improving the critical thinking skills of elementary school teacher candidates in a multicultural area. Using an explanatory sequential mixed methods design, this study began with a quantitative pretest–posttest measurement using an instrument based on the five dimensions of the California Critical Thinking Skills Test (CCTST), and continued with qualitative exploration through interviews and observations. A total of 173 students were divided into experimental and control groups. The results showed that the integration of the IBL approach and local cultural practices significantly improved critical thinking skills, especially in the dimensions of interpretation, analysis, and inference. The dimensions of evaluation and explanation experienced a more moderate increase, which was associated with the limited time of the intervention. Thematic analysis supported the quantitative findings and emphasized the role of cultural context in encouraging deep reflection and contextual awareness. The findings also revealed a gap in achievement between students from 3T and non-3T areas, indicating the need for scaffolding strategies and strengthening intercultural competence and social empathy. This study provides an empirical contribution to the development of a locally relevant and socially inclusive cultural-based pedagogical model. Implications include strengthening teacher education curricula, lecturer training, and policies that support the integration of local knowledge as a learning resource. Further research is recommended to be conducted longitudinally, develop culturally based assessment instruments, and explore other cultural practices as learning contexts.